Synthesis and Structure modification of Ionic Liquids to optimize their Thermoelectric Properties. (2018) - Pérez, Pilar; Uhl, Stephanie; Laux, Edith; Sanglard, Pauline; Marti, Roger; Keppner, Herbert; Vanoli, Ennio
Abstract: Ionic Liquids (IL) are organic salts with melting temperature typically below 100 °C. The unique properties of ionic liquids such as their excellent chemical and thermal stabilities, their low vapor pressure, their important ionic conductivity makes them interesting compounds in material science and especially in thermoelectric generators (TEGs) for medical, pharma, or electronic applications. A big advantage of ILs is the endless number of cation/anion combinations, which allows synthesizing task-specific ionic liquids for TEG applications. This paper describes the synthesis, physical and electrochemical characterization of novel IL for application in thermoelectric generators (TEGs). We discuss the optimization of the chemical structure of IL regarding their thermoelectric properties via a structure-activity relationship approach. The best ionic liquids are the protic ones with a Seebeck coefficient of 570.24 µV/K for methylammonium trifluoroacetate and -1424.56 µV/K for ethylammonium formate.